Kepatuhan Syariah pada Restrukturisasi Sukuk: Analisis dan Implikasi - Ilmiyah, Izzatul; Rosyidah, Irma; Mujib, Muhammad Abdul (Program Studi Perbankan Syariah STAI Senori Tuban, 2024)
One of the sharia financial instruments is sukuk which has the role of ownership of an asset, for this reason, sharia compliance plays an important role in discussing sharia compliance in the context of sukuk restructuring. This role is important because if there is a change in the conditions of the sukuk, the rights and obligations of holding the sukuk itself will be affected. This research uses a type of library research through theoretical, conceptual, and exploratory studies, and discussion of plans. The research results show that Sharia compliance ensures that sukuk restructuring must lead to sharia principles. Compliance is the foundation that ensures sukuk restructuring continues to run in accordance with guidelines maintains trust for investors and ensures the sustainability of the sharia financial industry. The implications of Sharia compliance on sukuk restructuring are Sharia compliance on sukuk investment, securities crowdfunding, the role of technology on crowdfunding platforms, education, and research.